(3GdTaGA HJYQja Mbhb GdoeUWaj (B((3Udi Gddg Ydjg hSde(B)s - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s
(3ChdgG (B:s
(3GdHGH GdKGfj ai dRhe eMHJg s
(3BNQgG (B:s
(3gfG GfJgi Gdbhd HfG ajeG MQQfGg hUdhGJg Ydi fHjg eMeO hYdi Bdg hSde JSdjeG s
(3fSNI NGeSIs
(3GdfUa GdKGfjs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
Keywords: (3GdJGQjNs